I think it’s D. (x+6, y-4)
because you go right on the x and down on the y
Both fractions have the same denominator so it's going to be easy. First set up your equation:
![3 \frac{3}{5} + 9 \frac{3}{5}](https://tex.z-dn.net/?f=%203%20%5Cfrac%7B3%7D%7B5%7D%20%2B%209%20%5Cfrac%7B3%7D%7B5%7D%20%20)
Add the whole numbers:
![3 + 9 = 12](https://tex.z-dn.net/?f=%203%20%2B%209%20%3D%2012%20)
Now add the fractions:
![\frac{3}{5} + \frac{3}{5} = \frac{6}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B5%7D%20%2B%20%5Cfrac%7B3%7D%7B5%7D%20%3D%20%5Cfrac%7B6%7D%7B5%7D%20%20%20)
add both together:
![12 + \frac{6}{5} = 12 \frac{6}{5}](https://tex.z-dn.net/?f=%2012%20%2B%20%5Cfrac%7B6%7D%7B5%7D%20%3D%2012%20%5Cfrac%7B6%7D%7B5%7D%20%20%20%20)
is an improper fraction so change it:
![12 \frac{6}{5} = 13 \frac{1}{5}](https://tex.z-dn.net/?f=%2012%20%5Cfrac%7B6%7D%7B5%7D%20%3D%2013%20%5Cfrac%7B1%7D%7B5%7D%20%20%20)
Since 6 is one more than 5, add 1 to the whole number and subtract the numerator and denominator(6 - 5 = 1) and make the remaining the new numerator. That leaves you with ![13 \frac{1}{5}](https://tex.z-dn.net/?f=%2013%20%5Cfrac%7B1%7D%7B5%7D%20%20)
Your answer is ![13 \frac{1}{5}](https://tex.z-dn.net/?f=%2013%20%5Cfrac%7B1%7D%7B5%7D%20%20)
Answer:
g(-3) = 0
Step-by-step explanation:
hello :
g(-3) = (-3)² + 3(-3) = 9-9 =0
Answer:
x=6
Step-by-step explanation:
In a square, its angles are all 90 degrees. So, cutting a square in half into two triangles from corner to corner produces 45 degree angles on both sides. Since the triangles are now 45-45-90 triangles, we can use the rule where the hypotenuse of the triangle is equal to the square root of 2 times the length of either side. So, the side length is 6.